2018
DOI: 10.1002/cctc.201801139
|View full text |Cite
|
Sign up to set email alerts
|

Biocatalytical Asymmetric Sulfoxidation by Identifying Cytochrome P450 from Parvibaculum Lavamentivorans DS‐1

Abstract: Cytochrome P450 monooxygenases (P450s) catalyzed asymmetric sulfoxidation represents a green route for the synthesis of valuable enantiopure sulfoxides, which are potentially interesting synthons in synthetic and pharmaceutical chemistry. Here the potential P450 and redox partner genes from Parvibaculum lavamentivorans DS‐1 are screened and co‐expressed in Escherichia coli host to construct twenty recombinant P450 strains. By testing the whole‐cell biooxidation of thioanisole, P450PL2 (CYP278A4) and P450PL7 (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 47 publications
(29 reference statements)
1
15
0
Order By: Relevance
“…15−21 We are interested in exploiting P450 monooxygenases for highly regio-and stereoselective oxidation reactions, including asymmetric hydroxylation 22−24 and sulfoxidation. 25 In particular, evolving P450pyr monooxygenase for the direct asymmetric hydroxylation of various alkylnitriles to access the corresponding β-hydroxy nitriles has been studied in our laboratory. Herein we describe our recent development of the highly enantioselective benzylic hydroxylation of 3-arylpropanenitriles by an engineered P450pyr monooxygenase to synthesize chiral β-hydroxy nitriles with up to >99% ee (Scheme 1).…”
Section: ■ Introductionmentioning
confidence: 99%
“…15−21 We are interested in exploiting P450 monooxygenases for highly regio-and stereoselective oxidation reactions, including asymmetric hydroxylation 22−24 and sulfoxidation. 25 In particular, evolving P450pyr monooxygenase for the direct asymmetric hydroxylation of various alkylnitriles to access the corresponding β-hydroxy nitriles has been studied in our laboratory. Herein we describe our recent development of the highly enantioselective benzylic hydroxylation of 3-arylpropanenitriles by an engineered P450pyr monooxygenase to synthesize chiral β-hydroxy nitriles with up to >99% ee (Scheme 1).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Not surprisingly, the majority of recent reports in this area concern the use of bacteria or fungi for sulfoxidation. 133 140 However, the use of isolated enzymes for enantioselective oxidation of sulfides in the past decade was also described by several groups. 141 144 Examples include monooxygenases, dioxygenase, and peroxidase.…”
Section: Preparation Of Chiral Nonracemic Sulfoxidesmentioning
confidence: 99%
“…Whole-cell preparations are operationally simpler and do not require addition of cofactors, although the nature of active catalytic species is not certain. Not surprisingly, the majority of recent reports in this area concern the use of bacteria or fungi for sulfoxidation. However, the use of isolated enzymes for enantioselective oxidation of sulfides in the past decade was also described by several groups. Examples include monooxygenases, dioxygenase, and peroxidase.…”
Section: Preparation Of Chiral Nonracemic Sulfoxidesmentioning
confidence: 99%
“…The general biocatalytic approaches for preparing chiral sulfoxides include asymmetric oxidation of sulfides and kinetic resolution of racemic ( rac ) sulfoxides. A great number of oxidases, including Baeyer–Villiger monooxygenases ( de Gonzalo et al, 2010 ; Rioz-Martínez et al, 2010 ; Bisagni et al, 2013 ; Bordewick et al, 2018 ; Zhang et al, 2018 ; Liu et al, 2021 ), cytochrome P450 monooxygenases ( Zhang et al, 2010 ; Wu et al, 2018 ), peroxidases ( Sangar et al, 2012 ; Bassanini et al, 2017 ), and dioxygenases ( Hibi et al, 2011 ; Shainsky et al, 2013 ), have been used for the synthesis of chiral sulfoxides. Meanwhile, biocatalytic kinetic resolution of rac -sulfoxides has also become an attractive approach for preparing chiral sulfoxides ( Anselmi et al, 2021 ), although it was relatively less reported.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have shown that higher substrate concentrations usually lead to significantly lower enzyme activities in the biocatalytic preparation of chiral sulfoxides ( Chen et al, 2014 ; de Gonzalo et al, 2017 ; de Gonzalo and Franconetti, 2018 ). In most biocatalytic processes, the initial substrate concentration was usually less than 30 mM ( Chen et al, 2014 ; Matsui et al, 2014 ; Wu et al, 2018 ; Zhang et al, 2018 ). The fact that a high concentration of unnatural substrates reduces enzyme activity makes substrate concentration be the bottleneck for biocatalytic preparation of chiral sulfoxides.…”
Section: Introductionmentioning
confidence: 99%